How Virtue Fits Within Business Ethics - Whetstone, J. Thomas (Journal of business ethics, 2001)
This paper proposes that managers add an attention to virtues and vices of human character as a full complement to moral reasoning according to a deontological focus on obligations to act and a teleological focus on consequences (a balanced tripartite approach). Even if the criticisms of virtue ethics cloud its use as a mononomic normative theory of justification, they do not refute the substantial benefits of applying a human character perspective – when done so in conjunction with also-imperfect act-oriented perspectives. An interactive tripartite approach is superior for meeting the complex requirements of an applied ethic. To illustrate how deficiencies of a "strong" virtue ethics formulation can be overcome by a balanced tripartite approach, this paper compares normative leadership paradigms (each based on a combination of virtue, deontology, or consequentialist perspectives) and the dangers inherent in each. The preferred paradigm is servant leadership, grounded in a tripartite ethic. Effective application of such an ethics approach in contemporary organizations requires further empirical research to develop a greater understanding of the moral language actually used. Meeting this challenge will allow academics better to assist practicing managers lead moral development and moral reasoning efforts.